Odpowiedzi

2009-12-31T18:22:40+01:00
A)
x+3/x*x²/x-9 = po skróceniu rzez x = (x+3)*x/(x-9)
b)
x³-8/2x-7 : x²+2x+4/4x²-49 =
= ((x-2)(x² +4x +4))/(2x - 7) : (x² +2x +4)/(2x +7)(2x - 7)
= ((x-2)(x² +4x +4))/(2x - 7) *(2x +7)(2x - 7)/ (x² +2x +4) =
= po skróceniu przez (2x - 7) mamy:
= (x-2)(x² +4x +4)*(2x +7)/(x² +2x +4)

c)2x/x-4 : x²/x²-16 = 2x/(x-4) * (x-4)(x+4)/x² =
= po skróceniu przez x oraz przez (x - 4)
= 2*(x +4)/x

d)21x+x²/x⁴-1:x³-7x²/12x²-12 =
= x(21 +x)/(x-1)(x³ + x² +x +1) *12(x²-1)/7x² =
=x(21 +x)/(x-1)(x³ + x² +x +1) * 12(x + 1)(x -1)/7x²=
= po skróceniu przez x oraz (x-1) otrzymujemy:
= (21 +x)/(x³ + x² + x + 1) * 12(x + 1 )/ 7x
Najlepsza Odpowiedź!
2009-12-31T20:46:52+01:00
A)
(x+3)/x * x²/(x-9) = x(x+3)/(x-9)

b)
[(x³-8)/(2x-7)] : [(x²+2x+4)/(4x²-49)] =
= [(x-2)(x²+2x +4) / (2x-7)] * [(2x-7)(2x+7)/(x²+2x+4)] =
= (x-2)*(2x +7)

c)
[2x/(x-4)] : [x²/(x²-16)] = [2x/(x-4)] * [(x-4)(x+4)/x²] =
= 2*(x+4) / x

d)
[(21x+x²)/(x⁴-1)] : [(x³-7x²)/(12x²-12)] =
= [x(21+x)/(x²-1)(x²+1)] * [12(x²-1)/x²(x-7)] =
= [(21 +x)/(x²+1)] * [12/x(x-7)]
1 5 1